2015
DOI: 10.1097/md.0000000000000669
|View full text |Cite
|
Sign up to set email alerts
|

Medium-Based Noninvasive Preimplantation Genetic Diagnosis for Human α-Thalassemias-SEA

Abstract: To develop a noninvasive medium-based preimplantation genetic diagnosis (PGD) test for α-thalassemias-SEA.The embryos of α-thalassemia-SEA carriers undergoing in vitro fertilization (IVF) were cultured. Single cells were biopsied from blastomeres and subjected to fluorescent gap polymerase chain reaction (PCR) analysis; the spent culture media that contained embryo genomic DNA and corresponding blastocysts as verification were subjected to quantitative-PCR (Q-PCR) detection of α-thalassemia-SEA. The diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 30 publications
0
53
0
Order By: Relevance
“…Notably, the development of a noninvasive medium-based PGD test for α-thalassemias-SEA was recently published by Wu et al . [18], corroborating the potential for noninvasive approaches.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Notably, the development of a noninvasive medium-based PGD test for α-thalassemias-SEA was recently published by Wu et al . [18], corroborating the potential for noninvasive approaches.…”
Section: Discussionmentioning
confidence: 64%
“…However, future studies with higher number of samples, the use of molecular methods with lower detection limits (e.g., digital PCR) or the evaluation of different target sequences coupled with linked markers may provide improvement in detection rates, making the extracellular matrices acceptable for PGD applications, therefore avoiding invasive procedures on the embryo. This perspective could be realistic as evidenced by a recently published work focusing on α-thalassemia [18]. Moreover, noninvasive PGD and/or embryo sexing should also be useful in the breeding and dairy industry, allowing fast selection of the preferred animal embryos.…”
Section: Future Perspectivementioning
confidence: 99%
“…Similarly, DNA isolated from media culturing α-thalassemias -SEA carrier embryos had significantly higher diagnosis efficiency compared to blastomere biopsy [16]. However, this method still needs to be further validated by eliminating potential contamination and providing more robust evidences in PGD/PGS.…”
Section: Bf Samplingmentioning
confidence: 96%
“…Palini et al (23) reported the observation of the existence of DNA in the blastocoele fluid, Gianaroli et al (24) performed a pilot study on chromosome screening using blastocentesis, and Stigliani et al (25,26) observed genomic and mitochondria DNA contents in the culture medium, which were correlated with embryo quality. Wu et al (27) reported the PCR detection of the secreted genomic DNA in the culture medium for preimplantation…”
mentioning
confidence: 99%